Photonic textiles for pulse oximetry - Markus Rothmaier; Bärbel Selm; Sonja Spichtig; Daniel Haensse; Martin Wolf (2008)
Biomedical sensors, integrated into textiles would enable monitoring of many vitally important physiological parameters during our daily life. In this paper we demonstrate the design and performance of a textile based pulse oximeter, operating on the forefinger tip in transmission mode. The sensors consisted of plastic optical fibers integrated into common fabrics. To emit light to the human tissue and to collect transmitted light the fibers were either integrated into a textile substrate by embroidery (producing microbends with a nominal diameter of 0.5 to 2 mm) or the fibers inside woven patterns have been altered mechanically after fabric production. In our experiments we used a two-wavelength approach (690 and 830 nm) for pulse wave acquisition and arterial oxygen saturation calculation. We have fabricated different specimens to study signal yield and quality, and a cotton glove, equipped with textile based light emitter and detector, has been used to examine movement artifacts. Our results show that textile-based oximetry is feasible with sufficient data quality and its potential as a wearable health monitoring device is promising.